Pembinaan Praktik Hukum Islam Melalui Fiqih Sholat Bersanad Pada Masyarakat Desa Cermen Kecamatan Kedamean Kabupaten Gresik - Nanang Abdillah; Ach Khusnan; Kholisuddin Kholisuddin; Lilik Husniah; Eka Aditiya Agustina (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
This research aims to provide reinforcement to the community so that they can further strengthen their faith, namely through the development of Islamic law on the Islamic jurisprudence of prayer with the Sanad. Bersanad prayer is an activity that begins with learning and deepening and understanding the meaning of fardu prayer both from the perspective of the Shari'a and from the essence. Prayer is the pillar of religion. Praying with a sanad does not mean that people have not had a sanad during their prayers. What is meant by bersanad prayer is that we try to connect our prayer practice to our teachers and the ulama who themselves got it from their teachers up to the prophet Muhammad SAW. We carried out this research by observing the people of Cermen village, Kedamean sub-district, Gresik district. The method used in this research is the PAR (Participatory Action Research) method. The stages of assisting the implementation of the PAR method in the Cermen village community use 3 stages, namely the preparation stage, implementation stage, and evaluation stage.